Preparation of hard carbonized negative electrode material based on petroleum coke (green coke) and application of hard carbonized negative electrode material to sodium ion battery

By preoxidizing petroleum coke (generated coke) in an oxygen-containing atmosphere and carbonizing at high temperature under an inert atmosphere, a hard carbonized negative electrode material with excellent electrochemical properties was prepared, which solved the problem that petroleum coke (generated coke) cannot be directly used in the negative electrode of sodium ion battery in the prior art, and large-scale industrial production with simple process and low cost is achieved.

CN119683607APending Publication Date: 2025-03-25BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510105493.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

At this stage, the source of hard carbon materials is mainly obtained from biomass materials, but due to the diversity, complexity and instability of biomass materials, its application as the negative electrode of sodium ion battery is full of unknowns. Petroleum coke (generic coke) cannot be directly used as the negative electrode of sodium ion battery due to its small spacing and easy graphitization.

Method used

Petroleum coke (generated coke) is preoxidized in an oxygen-containing atmosphere and carbonized at high temperature under an inert atmosphere to obtain a hard carbonized material, reducing the degree of graphitization, thereby preparing a petroleum coke (generated coke) hard carbonized negative electrode material with excellent electrochemical properties.

Benefits of technology

Through this process, the prepared petroleum coke (generated coke) hard carbonized anode material has excellent electrochemical properties, is suitable for sodium ion batteries, and is simple in process and low in cost, and can be used for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683607A_ABST
    Figure CN119683607A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of a hard carbonized negative electrode material based on petroleum coke (green coke) and application of a sodium ion battery. According to the invention, petroleum coke (green coke) is used as a raw material, pre-oxidation and high-temperature carbonization are carried out in an oxygen-containing atmosphere to obtain a hard carbonized negative electrode material, and the hard carbonized negative electrode material is used for preparing the low-cost sodium ion battery. The method is simple in preparation process, green and environment-friendly in raw material and suitable for batch production, and the prepared hard carbonized material has excellent electrochemical performance when applied to the sodium-ion battery and can be used as a sodium-ion battery negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to the preparation of a hard carbonized negative electrode material based on petroleum coke (green coke) and the application of the material in a sodium ion battery. Background Art

[0002] With the introduction of various new energy storage policies, lithium-ion batteries are now widely used in energy storage systems. Sodium-ion batteries have similar physical and chemical properties to lithium-ion batteries, and the total sodium reserves are abundant and the price is low, so sodium-ion batteries are high-quality candidates for large-scale energy storage. Negative materials are crucial in sodium-ion batteries. Hard carbon materials are a class of negative electrode materials with great application prospects. Because the large number of defects, graphite microcrystalline areas, pore structures and functional groups unique to hard carbon materials are beneficial to the storage of sodium ions, they have a high reversible specific capacity. At present, the source of hard carbon materials is mainly obtained from biomass materials. However, due to the diversity, complexity and instability of biomass materials, their application as negative electrodes for sodium-ion batteries is full of unknowns. Petroleum coke (green coke), as a by-product of the petrochemical industry, has the advantages of stable sources, low prices and stable structures. However, petroleum coke (green coke) cannot be directly used as a negative electrode material for sodium-ion batteries due to its small spacing and easy graphitization. At present, it has not been applied to the negative electrode of sodium-ion batteries. Therefore, petroleum coke (green coke) can be processed to inhibit graphitization and is expected to be used in sodium ion batteries. Summary of the invention

[0003] In order to solve the above problems, the present invention proposes a preparation method of hard carbonized negative electrode material based on petroleum coke (green coke) and application in sodium ion battery.

[0004] The present invention provides a method for preparing a hard carbonized negative electrode material based on petroleum coke (green coke) and its application in a sodium ion battery. The petroleum coke (green coke) is pre-oxidized in an oxygen-containing atmosphere and carbonized at a high temperature in an inert atmosphere to obtain a hard carbonized material.

[0005] In a first aspect, the method for preparing a hard carbonized negative electrode based on petroleum coke (green coke) comprises the following steps:

[0006] Step 1): Pre-oxidize petroleum coke (green coke) in air or oxygen at a temperature of 100-700°C, a time of 2-24h, and a heating rate of 1-10°C / min.

[0007] Step 2): The pre-oxidized powder obtained in step 1) is heated to 800-1500°C under an inert atmosphere, the carbonization time is 1-10h, the heating rate is 1-10°C / min, and the hard carbonized material is obtained, and the inert gas is at least one of nitrogen or argon.

[0008] In the second aspect, a hard carbonized negative electrode material based on petroleum coke (green coke) is prepared using the method for preparing a hard carbonized negative electrode based on petroleum coke (green coke) described in the first aspect.

[0009] In a third aspect, a negative electrode sheet for a sodium ion battery is provided.

[0010] It includes a hard carbonized negative electrode material based on petroleum coke (green coke) as described in the second aspect.

[0011] A fourth aspect is a sodium ion secondary battery.

[0012] Includes the negative electrode sheet described in the third aspect.

[0013] The beneficial effects of the present invention are as follows:

[0014] (1) The present invention provides a hard carbonized negative electrode material based on petroleum coke (green coke) and its application in sodium ion batteries. The petroleum coke (green coke) is pre-oxidized in air or oxygen to obtain a pre-oxidized powder. The pre-oxidized powder is carbonized at high temperature under inert atmosphere conditions to obtain a hard carbonized negative electrode material based on petroleum coke (green coke); the petroleum coke (green coke) is pre-oxidized in air or oxygen atmosphere to cause a cross-linking reaction between the petroleum coke (green coke) and oxygen to reduce the degree of graphitization, thereby preparing a petroleum coke (green coke) hard carbonized negative electrode material with excellent electrochemical properties;

[0015] (2) The present invention provides a method for preparing a hard carbonized negative electrode material based on petroleum coke (green coke) and its application in sodium ion batteries. The process is simple, low-cost and can be used for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 : is the X-ray diffraction pattern (XRD) of the hard carbonized negative electrode material based on petroleum coke (green coke) prepared in Examples 1, 2, 3 and 4.

[0017] Figure 2 This is a scanning electron microscope image (SEM) of the hard carbonized negative electrode material based on petroleum coke (green coke) prepared in Example 1.

[0018] Figure 3 This is a scanning electron microscope image (SEM) of the hard carbonized negative electrode material based on petroleum coke (green coke) prepared in Example 2.

[0019] Figure 4 This is a scanning electron microscope (SEM) image of the hard carbonized negative electrode material based on petroleum coke (green coke) prepared in Example 3.

[0020] Figure 5 This is a scanning electron microscope image (SEM) of the hard carbonized negative electrode material based on petroleum coke (green coke) prepared in Example 4.

[0021] Figure 6 This is a scanning electron microscope (SEM) image of the negative electrode material prepared in Comparative Example 1.

[0022] Figure 7 It is a 0.2C cycle performance diagram of Example 1 and Comparative Example 1 in a sodium ion battery.

[0023] Figure 8 It is a 0.2C cycle performance diagram of Example 2 and Comparative Example 1 in a sodium ion battery.

[0024] Fig. 9 It is a 0.2C cycle performance diagram of Example 3 and Comparative Example 1 in a sodium ion battery.

[0025] Fig.10 It is a 0.2C cycle performance diagram of Example 4 and Comparative Example 1 in a sodium ion battery. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] This embodiment provides a method for preparing a hard carbonized negative electrode material based on petroleum coke (green coke) and applying it to a sodium ion battery.

[0029] The preparation steps are as follows: pre-oxidize petroleum coke (green coke) in air at a temperature of 150°C, an oxidation time of 12h, and a heating rate of 3°C / min to obtain a pre-oxidized material; heat the pre-oxidized material to 1000°C in an argon atmosphere at a heating rate of 3°C / min and a holding time of 3h to obtain a hard carbonized negative electrode material based on petroleum coke (green coke); the XRD spectrum of the prepared petroleum coke (green coke) hard carbonized negative electrode material is as follows: Figure 1 As shown, the appearance is Figure 2 shown.

[0030] Assembly and electrochemical performance test of button batteries:

[0031] The prepared hard carbonized negative electrode material based on petroleum coke (raw coke) was mixed with Super P and PVDF in a mass ratio of 80:10:10, and an appropriate amount of N-methyl-2-pyrrolidone NMP was added to the mixed sample and stirred to form a uniform slurry. The obtained slurry was coated on a copper foil, vacuum dried at 100°C for 12 hours, and cut to obtain a negative electrode sheet with a diameter of 11 mm; metallic sodium was used as the counter electrode, a glass fiber filter membrane (Whatman GF / C) was used as the diaphragm, a 1 mol / LNaPF6 solution of ethylene glycol dimethyl ether (DME) was used as the electrolyte, and a stainless steel shell was used as the shell to assemble a 2025 button battery; the charge and discharge test was completed under the Xinwei battery system, the test voltage range was 0.01-2.6V, the test temperature was room temperature, the test current density of the first 3 cycles was 0.1C (1C=300mA / g), and then the charge and discharge test was carried out at a current density of 0.2C.

[0032] Experimental results: The first cycle discharge capacity is 433.79mAh / g, and the discharge capacity after 50 cycles is 194.42mAh / g ( Figure 7 ).

[0033] Example 2

[0034] This embodiment provides a method for preparing a hard carbonized negative electrode material based on petroleum coke (green coke) and applying it to a sodium ion battery.

[0035] The preparation steps are as follows: pre-oxidize petroleum coke (green coke) in air at a temperature of 300°C, an oxidation time of 12h, and a heating rate of 3°C / min to obtain a pre-oxidized material; heat the pre-oxidized material to 1000°C in an argon atmosphere at a heating rate of 3°C / min and a holding time of 3h to obtain a hard carbonized negative electrode material based on petroleum coke (green coke); the XRD spectrum of the prepared petroleum coke (green coke) hard carbonized negative electrode material is as follows: Figure 1 As shown, the appearance is Figure 3 shown.

[0036] Assembly and electrochemical performance test of button batteries:

[0037] The prepared hard carbonized negative electrode material based on petroleum coke (raw coke) was mixed with Super P and PVDF in a mass ratio of 80:10:10, and an appropriate amount of N-methyl-2-pyrrolidone NMP was added to the mixed sample and stirred to form a uniform slurry. The obtained slurry was coated on a copper foil, vacuum dried at 100°C for 12 hours, and cut to obtain a negative electrode sheet with a diameter of 11 mm; metallic sodium was used as the counter electrode, a glass fiber filter membrane (Whatman GF / C) was used as the diaphragm, a 1 mol / LNaPF6 solution of ethylene glycol dimethyl ether (DME) was used as the electrolyte, and a stainless steel shell was used as the shell to assemble a 2025 button battery; the charge and discharge test was completed under the Xinwei battery system, the test voltage range was 0.01-2.6V, the test temperature was room temperature, the test current density of the first 3 cycles was 0.1C (1C=300mA / g), and then the charge and discharge test was carried out at a current density of 0.2C.

[0038] Experimental results: The first cycle discharge capacity is 400.99mAh / g, and the discharge capacity after 50 cycles is 196.6mAh / g ( Figure 8 ).

[0039] Example 3

[0040] This embodiment provides a method for preparing a hard carbonized negative electrode material based on petroleum coke (green coke) and applying it to a sodium ion battery.

[0041] The preparation steps are as follows: pre-oxidize petroleum coke (green coke) in air at a temperature of 400°C, an oxidation time of 12h, and a heating rate of 3°C / min to obtain a pre-oxidized material; heat the pre-oxidized material to 1000°C in an argon atmosphere at a heating rate of 3°C / min and a holding time of 3h to obtain a hard carbonized negative electrode material based on petroleum coke (green coke); the XRD spectrum of the prepared petroleum coke (green coke) hard carbonized negative electrode material is as follows: Figure 1 As shown, the appearance is Figure 4 shown.

[0042] Assembly and electrochemical performance test of button batteries:

[0043] The prepared hard carbonized negative electrode material based on petroleum coke (raw coke) was mixed with Super P and PVDF in a mass ratio of 80:10:10, and an appropriate amount of N-methyl-2-pyrrolidone NMP was added to the mixed sample and stirred to form a uniform slurry. The obtained slurry was coated on a copper foil, vacuum dried at 100°C for 12 hours, and cut to obtain a negative electrode sheet with a diameter of 11 mm; metallic sodium was used as the counter electrode, a glass fiber filter membrane (Whatman GF / C) was used as the diaphragm, a 1 mol / LNaPF6 solution of ethylene glycol dimethyl ether (DME) was used as the electrolyte, and a stainless steel shell was used as the shell to assemble a 2025 button battery; the charge and discharge test was completed under the Xinwei battery system, the test voltage range was 0.01-2.6V, the test temperature was room temperature, the test current density of the first 3 cycles was 0.1C (1C=300mA / g), and then the charge and discharge test was carried out at a current density of 0.2C.

[0044] Experimental results: The first cycle discharge capacity is 443.16 mAh / g, and the discharge capacity after 50 cycles is 214.38 mAh / g ( Fig. 9 ).

[0045] Example 4

[0046] This embodiment provides a method for preparing a hard carbonized negative electrode material based on petroleum coke (green coke) and applying it to a sodium ion battery.

[0047] The preparation steps are as follows: pre-oxidize petroleum coke (green coke) in air at a temperature of 550°C, an oxidation time of 12h, and a heating rate of 3°C / min to obtain a pre-oxidized material; heat the pre-oxidized material to 1000°C in an argon atmosphere at a heating rate of 3°C / min and a holding time of 3h to obtain a hard carbonized negative electrode material based on petroleum coke (green coke); the XRD spectrum of the prepared petroleum coke (green coke) hard carbonized negative electrode material is as follows: Figure 1 As shown, the appearance is Figure 5 shown.

[0048] Assembly and electrochemical performance test of button batteries:

[0049] The prepared hard carbonized negative electrode material based on petroleum coke (raw coke) was mixed with Super P and PVDF in a mass ratio of 80:10:10, and an appropriate amount of N-methyl-2-pyrrolidone NMP was added to the mixed sample and stirred to form a uniform slurry. The obtained slurry was coated on a copper foil, vacuum dried at 100°C for 12 hours, and cut to obtain a negative electrode sheet with a diameter of 11 mm; metallic sodium was used as the counter electrode, a glass fiber filter membrane (Whatman GF / C) was used as the diaphragm, a 1 mol / LNaPF6 solution of ethylene glycol dimethyl ether (DME) was used as the electrolyte, and a stainless steel shell was used as the shell to assemble a 2025 button battery; the charge and discharge test was completed under the Xinwei battery system, the test voltage range was 0.01-2.6V, the test temperature was room temperature, the test current density of the first 3 cycles was 0.1C (1C=300mA / g), and then the charge and discharge test was carried out at a current density of 0.2C.

[0050] Experimental results: The first cycle discharge capacity is 406.78 mAh / g, and the discharge capacity after 50 cycles is 197.96 mAh / g ( Fig.10 ).

[0051] Comparative Example 1

[0052] This comparative example provides a petroleum coke (raw coke) carbon material and its preparation method and application

[0053] The preparation steps are as follows: petroleum coke (green coke) is heated to 1000°C in an argon atmosphere at a heating rate of 3°C / min and a holding time of 3h to obtain a petroleum coke (green coke) carbon material. The morphology of the prepared petroleum coke (green coke) based hard carbon is as follows: Figure 6 shown.

[0054] As in Example 1, the electrodes were prepared, the battery was assembled, and electrochemical tests were performed.

[0055] Experimental results: The first cycle discharge capacity is 379.41mAh / g, and the discharge capacity after 40 cycles is 179.79mAh / g ( Figure 7-10 ).

Claims

1. A preparation method of a hard carbonized negative electrode material based on petroleum coke (green coke), characterized in that: Petroleum coke (green coke) is used as a carbon source, pre-oxidized in an oxygen-containing atmosphere, and then carbonized at a high temperature in an inert atmosphere to obtain a hard carbonized material.

2. The preparation of a hard carbonized negative electrode material based on petroleum coke (green coke) according to claim 1, characterized in that: The following steps are involved: The petroleum coke (green coke) is pre-oxidized in an oxygen-containing atmosphere and carbonized at a high temperature in an inert atmosphere to obtain a hard carbonized material.

3. The preparation method according to claim 2, characterized in that: The pre-oxidation temperature is 100-700°C, preferably 200-500°C, the pre-oxidation time is 2-24h, preferably 9-15h, and the heating rate is 1-10°C / min, preferably 2-5°C / min.

4. The preparation method according to claim 2, characterized in that: The high temperature carbonization temperature is 800-1500°C, preferably 900-1300°C, the carbonization time is 1-10h, preferably 2-5h, the heating rate is 1-10°C / min, preferably 2-5°C / min, the oxygen-containing atmosphere is air or oxygen, and the inert atmosphere is at least one of nitrogen or argon.

5. A hard carbonized negative electrode material based on petroleum coke (green coke) as described in claims 1-4.

6. A negative electrode plate for a sodium ion battery, comprising: A current collector, a binder coated on the current collector, a conductive agent and a hard carbonized negative electrode material based on petroleum coke (green coke) as claimed in claim 5.

7. A sodium ion secondary battery comprising the negative electrode sheet of the sodium ion battery according to claim 6.